Price relationships and market linkages of by-product critical metals across multiple time scales: A case study of copper and cobalt - Hui, SU; Qiaosheng, WU; Jinhua, CHENG; Zhiwei, BI (Zi yuan ke xue, 2025)
[Objective] Compared to conventional bulk metal markets, by-product critical metal markets are still in a rapid growth phase, where market fluctuations frequently occur due to periodic supply-demand mismatches. These markets exhibit more intense price volatility and more complex linkages. Investigating the linkage effects in these markets can provide valuable reference for market participants to better understand market dynamics and respond promptly to the impact of price fluctuations and volatility. [Methods] This study selected copper and cobalt, two by-product critical metals, as the research objects. Based on the ensemble empirical mode decomposition, nonlinear Granger causality tests, DCC-GARCH model, and MSVAR model, the study analyzed the bidirectional price relationships, dynamic market associations, market linkage evolution, and their influencing factors across different time scales from 2008 to 2022. [Results] (1) The price relationship between copper and cobalt exhibited significant nonlinearity, with time-varying and heterogeneous characteristics. (2) The markets of copper and cobalt had strong linkages, and volatility spillover effects showed temporal heterogeneity. (3) In the short term, copper-cobalt market linkages transitioned among three regimes: stable, low volatility, and high volatility. In the long term, they were mostly in high-volatility or stable regimes. (4) Speculation and geopolitical risk factors were key influencing factors of copper-cobalt market linkages in the short term, while supply and long-term economic development trends were key influencing factors in the long term. [Conclusion] The price relationship between copper and cobalt exhibits significant nonlinear characteristics across multiple time scales, with time-varying and heterogeneous properties. Copper-cobalt market linkages are strong, and volatility spillover effects vary with the time scale. In the short term, the market linkages transition among three regimes: stable, low volatility, and high volatility. After 2017, high volatility has become the norm, largely driven by geopolitical risks. In the long term, the market has mostly remained in stable and high-volatility regimes, with a full shift to high volatility after 2021, increasingly influenced by macroeconomic trends and supply-demand fundamentals.